Traditional Chinese Medicine as a Treatment for Rheumatoid Arthritis: From Empirical Practice to Evidence-Based Therapy. (October 2019) - Pan, Hu-Dan; Xiao, Yao; Wang, Wan-Ying; Ren, Ru-Tong; Leung, Elaine Lai-Han; Liu, Liang
Abstract: Rheumatoid arthritis (RA) is a common autoimmune condition with an elusive etiology. Conventional and biological disease-modifying drugs sometimes fail or produce only partial responses. Traditional Chinese medicine (TCM) has long been used in China as a treatment for RA and is achieving ever-increasing acceptance worldwide. TCM treatments are traditionally guided by the theory of treatment based on TCM syndrome differentiation; however, they remain a matter of empirical practice relying on TCM theories and doctors' own experience, which places severe restrictions on worldwide TCM application. Nevertheless, TCM is a treasure trove for drug discovery, particularly as a treatment for complicated human conditions. The discoveries of artemisinin as a treatment for malaria and of TCM–arsenic trioxide (As2 O3 ) combination therapy as a treatment for acute promyelocytic leukemia (APL) are excellent examples of the great value of TCM. Regarding RA treatments, many Chinese medicinal herbs and their formulas, extracts, ingredients, and even single compounds have been used in clinical applications. Several Chinese proprietary medicines (CPMs) derived from TCM formulas or herbal bioactive components, such as the controlled-release ZhengQingFengTongNing (ZQFTN) Tablets, Tripterygium Glycoside Tablets, and Total Glucosides of Peony (TGP) Capsules, have been included in the National Health Insurance Directory of China, and show comparable therapeutic efficacies to those of western chemical drugs with fewer side effects. As TCM research has advanced, particularly in the use of multidisciplinary technologies, the scientific foundations and characteristics of the use of TCM to treat RA have been revealed, and the quality of TCM treatments have been increasingly enhanced. However, TCM generally lacks sufficient clinical and laboratory data to be consistent with international standards for quality, safety, and efficacy in order to support its application worldwide. Therefore, intensive basic and clinical studies on TCM are required. In particular, investigations that use cutting-edge technologies in analytical chemistry, biology, and biomedical sciences, and the development of randomized clinical trials (RCTs) and personalized pragmatic randomized controlled trials (PPRCTs) are necessary. Researchers should also collaborate to advance TCM from empirical practice to evidence-based therapy, thus consistently promoting TCM development and globalization in a vital, beneficial, and contributable manner.